Obesity: Increased risk of chronic non-communicable diseases in South Africa and India - C Srinivas, Sunitha; Dukhi, Natisha; Wrench, Wendy (Indian Journal of Pharmacy Practice)
Although the incidence of chronic non-communicable diseases (CNCDs) is increasing, CNCDs were not included in the United Nations Millennium Development Goals (2000) which focussed on the major global challenges of communicable diseases, child and maternal health and poverty-related issues along with strengthening health policies. Although some countries have since incorporated CNCDs into the MDGs, this has not happened globally, a matter which requires urgent attention. Obesity and physical inactivity are risk factors for some CNCDs such as cardiovascular disease and diabetes. The incidence of these risk factors is increasing in developing countries such as India and South Africa with an increase in urbanization and the influence of Westernization playing an important role. Cultural influences may also play a role in the increase in obesity e.g. in South Africa, being overweight or obese is associated with affluence and happiness in some cultures. The World Health Assembly Global Strategy on Diet, Physical Activity and Health (2004) provides guidelines to reduce global disease, deaths and CNCD risk factors, with an emphasis on improvement of diet and physical activity promotion. To reduce the incidence of CNCDs, these guidelines should be implemented using a multi-sectoral and multi-stakeholder approach.
Keywords: Obesity; chronic non-communicable diseases; Millennium Development Goals